Carbonate-Associated Organic Matter Is a Detectable Dissolved Organic Matter Source in a Subtropical Seagrass Meadow - Zeller, Mary A.; Van Dam, Bryce R.; Lopes, Christian; Kominoski, John S. (Frontiers in Marine Science, 2020)
Seagrasses can enhance carbonate sediment dissolution on diel timescales through oxidation of the rhizosphere and production of acidic exudates of dissolved organic matter (DOM). Carbonates can also associate with DOM either from biogenesis or later adsorption. However, the impact of mineral dissolution on the release of carbonate-associated DOM and on surface water DOM quantity and quality is unclear. We analyzed sub-daily changes in EEMS-PARAFAC components (excitation-emission matrices with parallel factor analysis), fluorescence, and absorbance properties of surface waters over adjacent low- and high-density (LD and HD) Thalassia testudinum seagrass meadows in Florida Bay, USA. We compared fluorescent DOM characteristics of seagrass leaves, acidified (dissolved) sediment leachates, and surface water samples collected from the HD and LD sites with surface water from a nearby mangrove island. The HD site was higher in humic-like PARAFAC components, specific ultraviolet absorbance, and humification index. We did not observe changes in EEMs indices or PARAFAC components with cumulative photosynthetically active radiation, indicating that photodegradation was unlikely to contribute to temporal variability in DOM. Similarities among DOM optical properties from acidified sediment leachates and surface waters at both sites suggest the importance of carbonate dissolution/reprecipitation for DOM cycling, while seagrass leaf leachates were markedly dissimilar to surface waters. We observed similarities among the acidified sediment leachate, surface water, and porewater elsewhere in Florida Bay, indicating dynamic coupling between these DOM pools. From this short study, Florida Bay DOM cycling appears to be more sensitive to carbonate dissolution than to additional photodegradation or authigenic seagrass leaching.